Different risks of hemorrhage in patients with elevated international normalized ratio from chronic liver disease versus warfarin therapy, a population‐based retrospective cohort study. (26th May 2022) - Afzal, Amber; Gage, Brian F.; Suhong, Luo; Schoen, Martin W.; Korenblat, Kevin; Sanfilippo, Kristen M.
Abstract: Background: Patients with chronic liver disease (CLD) often present with an elevated international normalized ratio (INR). Although elevated INR reflects a higher risk of hemorrhage among warfarin users, its clinical significance in CLD patients is less clear. Objectives: We used Veterans Health Administration data to quantify the association between INR and (non‐variceal) hemorrhage in patients with CLD compared to warfarin users. Methods: We performed a multivariate competing risk analysis to study the association between INR and hemorrhage in the two cohorts. We used an interaction term between INR and cohort (CLD/warfarin users) to test if INR had different effects on hemorrhage in the two cohorts. Results: Data from 80 134 patients (14, 412 with CLD and 65, 722 taking warfarin) were analyzed. The effect of INR on the risk of hemorrhage differed between CLD patients and warfarin users (interaction P < .001). As INR increased above 1.5, the adjusted hazard ratio (aHR) for hemorrhage in CLD patients increased to 2.25 but remained fairly constant with further elevation of INR values. In contrast, the risk of hemorrhage in patients taking warfarin remained low with INR in the subtherapeutic (INR <2.0) and therapeutic ranges (INR 2.0–3.0), and increased exponentially with INR in the supratherapeutic range (aHR 1.64 with INR >3.0–3.5, and 4.70 with INR >3.5). Conclusions: The relationship between INR and risk of hemorrhage in CLD patients is different from that in warfarin users. Caution should be exercised extrapolating data from warfarin users to make clinical decisions in CLD patients.